THEORETICAL FOUNDATIONS OF INCREASING PRODUCTION EFFICIENCY - O’ljayev Sardor Ismoilovich (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract. The article examines the main prospective directions of increasing the efficiency of production activity. It was determined which principles and ways contribute to increasing the efficiency of the enterprise's production activity. The issue of ways to increase the efficiency of the personnel's work was considered.